Placental alterations in structure and function in intra‐uterine growth‐retarded horses. (6th November 2017) - Robles, M.; Peugnet, P. M.; Valentino, S. A.; Dubois, C.; Dahirel, M.; Aubrière, M.‐C.; Reigner, F.; Serteyn, D.; Wimel, L.; Couturier‐Tarrade, A.; Chavatte‐Palmer, P.
Summary: Background: Following embryo transfer (ET), the size and breed of the recipient mare can affect fetal development and subsequent post natal growth rate and insulin sensitivity in foals. Objectives: To investigate placental adaptation in pregnancies where increased or restricted fetal growth was induced through ET between Pony, Saddlebred and Draught horses. Study design: In vivo experiment. Methods: Control Pony (P, n = 21) and Saddlebred (S, n = 28) pregnancies were obtained by artificial insemination. Increased pregnancies were obtained by transferring Pony (P‐D, n = 6) and Saddlebred (S‐D, n = 8) embryos into Draught mares. Restricted pregnancies were obtained by transferring Saddlebred embryos into Pony mares (S‐P, n = 6). Placental weight and surface were recorded and samples collected for stereology and analysis of expression of genes involved in placental growth, vascularisation and nutrient transport. Data were analysed by linear model. Results: S‐P foals were growth retarded when compared with controls despite increased gestational length. Placental weight was reduced but placental surface density and volume fraction were increased. Placental expression of genes involved in growth and development and nutrient transfer was strongly reduced. In contrast, placental size and weight were increased in enhanced growth P‐D and S‐D foals. The trophoblastic surface density and the allantoic vessels surface density were decreased in P‐D and S‐D, respectively, both with very few modifications in gene expression. Main limitations: Control embryos were produced by artificial insemination whereas experimental embryos were produced by ET. Conclusions: Placental structure and gene expression are modified after ET into a smaller or larger breed than that of the embryo. These adaptations contribute to the observed phenotype of foal growth restriction or enhanced growth at birth.